2011
DOI: 10.1007/s11512-010-0124-2
|View full text |Cite
|
Sign up to set email alerts
|

Equidistribution of points via energy

Abstract: We study the asymptotic equidistribution of points with discrete energy close to Robin's constant of a compact set in the plane. Our main tools are the energy estimates from potential theory. We also consider the quantitative aspects of this equidistribution. Applications include estimates of growth for the Fekete and Leja polynomials associated with large classes of compact sets, convergence rates of the discrete energy approximations to Robin's constant, and problems on the means of zeros of polynomials with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The theorem of Erdős and Turán has been extended by several authors (see, for instance [3,2,19,20,21]). In particular, Mignotte showed that one can use the weaker norm M + in estimates like (1.3), see [19] and [2].…”
Section: Annular Discrepancies and Norms On Tmentioning
confidence: 99%
“…The theorem of Erdős and Turán has been extended by several authors (see, for instance [3,2,19,20,21]). In particular, Mignotte showed that one can use the weaker norm M + in estimates like (1.3), see [19] and [2].…”
Section: Annular Discrepancies and Norms On Tmentioning
confidence: 99%
“…His work originated several important directions in analysis and number theory. Certain number theoretic aspects of Schur's paper are discussed in detail in [18], while [19] emphasizes its analytic side as generalized by Fekete [5] and Szegő [25]. We review and develop some of these recent results on Schur's problems from [21].…”
Section: Integer Chebyshev Problemmentioning
confidence: 99%
“…and note that each Q n has simple zeros {z j,n } n j=1 at the roots of unity, and integer coefficients. Using number theoretic arguments, we show in Remark 2.8 of [19] that the degree of Q n is…”
Section: Means Of Zerosmentioning
confidence: 99%
“…It converges monotonically to the transfinite diameter of S 2 (in the logarithmic case), introduced in [PoSz31], which equals the logarithmic capacity exp(−W log ) of S 2 ; see [Pri11] for a recent account.…”
Section: The Logarithmic Casementioning
confidence: 99%